Polusi Udara dan Risiko Penyakit Akut pada Telinga, Hidung, dan Tenggorok: Studi Cross-Sectional di Jakarta Barat - Tjhin, Purnamawati; Melati, Tiara; Agustawan, Dwi; Abdillah, Fauzan (Jurnal Biomedika dan Kesehatan, 2025)
Background Air pollution, particularly in urban areas such as West Jakarta, is a major public health concern. Longterm exposure to pollutants, including particulate matter (PM) 2.5, can lead to respiratory problems, including acute otolaryngologic diseases. Outdoor workers, such as those involved in urban infrastructure maintenance, are more vulnerable to these conditions. This study aimed to assess the relationship among air pollution levels, mucociliary clearance function, and the prevalence of acute otolaryngologic diseases among outdoor workers in West Jakarta. Methods A cross-sectional study was conducted among 120 Public Infrastructure and Facility Maintenance (PPSU) workers in the Cengkareng, Rawa Buaya, and Cengkareng Timur sub-districts. Air quality was assessed using data from nearby monitoring stations, measuring PM2.5 levels and the Air Quality Index (AQI). Health assessments included anamnesis, patient-reported outcome questionnaires, saccharin transit test, and otorhinolaryngologic endoscopic assessments. Results The average PM2.5 level was 57.58 μg/m³ (high risk for respiratory issues), and the AQI was 144.71 µg/m³ (unhealthy). The saccharin transit time test averaged 427.29 seconds, with a mean nasal floor length of 63.76 mm. The prevalence of acute rhinopharyngitis was 59.2%, rhinosinusitis 8.3%, occupational rhinitis 9.2%, and vitamin D insufficiency 67.5%. However, no significant correlation was found between air pollution exposure, mucociliary function, and acute otolaryngologic diseases (p > 0.05). Conclusions Despite high exposure to air pollution, no significant relationship was observed between air pollution, mucociliary clearance, and acute otolaryngologic diseases among PPSU workers. Further studies with larger sample sizes and longitudinal designs are needed.